2011
DOI: 10.1371/journal.pone.0014519
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and Joint Analysis of Two Metagenomic Datasets from a Biogas Fermenter Obtained by 454-Pyrosequencing

Abstract: Biogas production from renewable resources is attracting increased attention as an alternative energy source due to the limited availability of traditional fossil fuels. Many countries are promoting the use of alternative energy sources for sustainable energy production. In this study, a metagenome from a production-scale biogas fermenter was analysed employing Roche's GS FLX Titanium technology and compared to a previous dataset obtained from the same community DNA sample that was sequenced on the GS FLX plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
140
1
17

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(173 citation statements)
references
References 73 publications
13
140
1
17
Order By: Relevance
“…Combining metaproteomic analyses and isotopic, chemical and molecular approaches, the present study provides one of the most comprehensive views of expressed biological functions during cellulosic waste methanisation, complementing the information gained from previous metagenomic or metatranscriptomic studies (for example, Krause et al, 2008;Schluter et al, 2008;Jaenicke et al, 2011;Rademacher et al, 2012;Zarkzewski et al, 2012). Using the complete UniprotKB database, over 500 protein functions were identified.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Combining metaproteomic analyses and isotopic, chemical and molecular approaches, the present study provides one of the most comprehensive views of expressed biological functions during cellulosic waste methanisation, complementing the information gained from previous metagenomic or metatranscriptomic studies (for example, Krause et al, 2008;Schluter et al, 2008;Jaenicke et al, 2011;Rademacher et al, 2012;Zarkzewski et al, 2012). Using the complete UniprotKB database, over 500 protein functions were identified.…”
Section: Discussionmentioning
confidence: 77%
“…Isotopic labelled substrates were exploited to identify the functional microbial groups catalysing the methanisation of cellulose using stable isotope probing (Li et al, 2009). Several metagenomic studies shed light on the identity of the functional groups and provided an extended catalogue of the catalytic potential (Krause et al, 2008;Schlü ter et al, 2008;Jaenicke et al, 2011;Rademacher et al, 2012). However, these approaches do not generate direct information on the expressed genes and associated metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation might be that our co-fermentation system was not at optimal condition. Some studies showed that hydrogenotrophic pathway prevailed in the co-digesters of agricultural waste (Jaenicke et al 2011). Acetoclastic methanogenesis may be a major pathway in some systems (Supaphol et al 2011), or both pathways were utilized for methanogenesis ).…”
Section: Discussionmentioning
confidence: 99%
“…Six genera of methanogens, Methanosarcina, Methanosaeta, Methanoculleus, Methanosphaera, Methanobrevibacter, and Methanobacterium, were found in the SS-AD. Certain studies showed that a hydrogenotrophic pathway prevailed in the digesters of agricultural waste (Jaenicke et al, 2011). Acetoclastic methanogenesis may be a major pathway in certain systems, or both pathways were utilized for methanogenesis (Li et al, 2013).…”
Section: Microbial Community Analysis By High-throughput Sequencingmentioning
confidence: 99%